PROSPECTS FOR DIGITALIZATION OF ART EDUCATION - Pereverzeva; Grigorieva; Grushina; Kruglova; Ovsyannikova (Revista Inclusiones, 2020)
The relevance of the study is due to the fact that in the framework of the state program of digitalization of all spheres of the life of Russians, the learning process in higher education institutions of art and culture has acquired a digital format. In this regard, this study is aimed at assessing the digitalization results of a modern university (using the example of the Higher School of Music of A. Schnittke (Institute) of the Russian State Social University and the trends in this process. The analysis of the results allows concluding that in Russia, the digitalization of higher education leads to an increase in the level of its quality, an increase in the level of mastery of programs by students, an expansion of the range of competencies and opportunities for them to obtain quality education for a wider circle of people.